Main belt asteroids taxonomical information from dark energy survey data - Carruba, V. [UNESP]; Camargo, J. I.B.; Aljbaae, S.; Ferreira, F. S.; Lin, E.; Figueiredo-Peixoto, V.; Banda-Huarca, M. V.; Pieres, A.; Boufleur, R. C.; Da Costa, L. N.; Abbott, T. M.C.; Aguena, M.; et al. (Oxford University Press (OUP), 2024)
While proper orbital elements are currently available for more than 1 million asteroids, taxonomical information is still lagging behind. Surveys like SDSS-MOC4 provided preliminary information for more than 100 000 objects, but many asteroids still lack even a basic taxonomy. In this study, we use Dark Energy Survey (DES) data to provide new information on asteroid physical properties. By cross-correlating the new DES data base with other data bases, we investigate how asteroid taxonomy is reflected in DES data. While the resolution of DES data is not sufficient to distinguish between different asteroid taxonomies within the complexes, except for V-type objects, it can provide information on whether an asteroid belongs to the C- or S-complex. Here, machine learning methods optimized through the use of genetic algorithms were used to predict the labels of more than 68 000 asteroids with no prior taxonomic information. Using a high-quality, limited set of asteroids with data on gri slopes and i - z colours, we detected 409 new possible V-type asteroids. Their orbital distribution is highly consistent with that of other known V-type objects.
Keywords: catalogues; celestial mechanics; minor planets, asteroids: general